Viability duration of pacu (Piaractus mesopotamicus) milt stored under refrigeration - Spica, L. N.; Oliveira, T. S. [UNESP]; Silva, A. F. [UNESP]; Herédia-Ribas, C. M. [UNESP]; Povh, J. A.; Batlouni, S. R. [UNESP]; Sanches, E. A. [UNESP] (FapUNIFESP (SciELO), 2024)
Cooling milt conserves viable spermatozoa to extend the period available for artificial fertilization and avoids the robust protocols and high costs associated with cryopreservation. Yet, the sperm quality curves of fresh and refrigerated milt have not yet been compared for pacu (Piaractus mesopotamicus), which is often used as a biological model. This study aimed to analyze the milt quality of male P. mesopotamicus across 24 h of refrigeration. Six adult males were induced with carp pituitary extract. Sperm movement, membrane integrity, and morphology was compared between extruded milt samples stored for 24 h under either ambient temperature or under refrigeration at 12.63 °C. Sperm motility differed significantly over time. After 24 h of storage, motility values were higher in refrigerated spermatozoa than in those kept at ambient temperature. Sperm cell survival rates did not differ 4–8 h post collection. After 16 h, refrigerated cells showed superior membrane integrity (82.05 ± 4.23%) compared to those stored at ambient temperature (66.98 ± 6.45%), maintaining this pattern up to 24 h. In terms of sperm morphology rate, milt from both treatment groups was still viable for use 8 h after collection. However, after 16 h of storage, both groups exhibited a large reduction in normality rates, and at 24 h, all milt were unfeasible. In conclusion, P. mesopotamicus milt can be stored up to 8 h after collection when refrigerated at 12.63 °C, without the use of extenders and/or cryoprotectants, maintaining enough quality for egg fertilization.
Duração da viabilidade do sêmen de pacu (Piaractus mesopotamicus) armazenado sob refrigeração
Keywords: chilled milt; computer-assisted sperm analysis; fish reproduction; rheophilic fish